Adaptive servoventilation improves cardiac dysfunction and prognosis in heart failure patients with sleep‐disordered breathing: a meta‐analysis. (22nd October 2015) - Wu, Xu; Fu, Cuiping; Zhang, Shuqi; Liu, Zilong; Li, Shanqun; Jiang, Liyan
Abstract: Background: Adaptive servoventilation (ASV) is a new therapeutic modality to treat sleep‐disordered breathing (SDB) especially for central sleep apnoea associated with Cheyne–Stokes respiration, whereas the role of ASV in SDB patients with heart failure (HF) is controversial. The purpose of this study was to evaluate the effects of ASV on these patients through a meta‐analysis of published data. Methods: A comprehensive literature search was performed to identify studies focused on ASV through databases, including PubMed, Medline, Embase, Cochrane Library and Web of science from 1950 to 2014. Parallel randomised controlled trials which compared ASV to other controls in HF and SDB patients with extractable data were meet our inclusion criteria. Random effects meta‐analysis models were applied using RevMan 5.2. Results: Seven studies involving 301 patients were recruited in the meta‐analysis. The weighted mean difference in apnoea hyponea index (−17.73 events/h, 95% CI, −21.85 to −2.94) and left ventricular ejection fraction (MD: 4.68, 95% CI, 2.74–6.63) both favored ASV compared to control conditions. The urinary noradrenaline level (MD: −32.18, 95%CI: −44.07 to −20.09) was decreased, while the exercise capacity measured by 6‐min walk distance (MD: 41.26, 95% CI, 17.06–65.45) was improved after ASV treatment. Whereas neither left ventricular end‐diastolic diameter (LVEDD) nor Epworth sleepiness‐scale score (ESS) significantly changed after ASV therapy. Conclusions: ASV is superior to other therapy, as it can result in good consequences for patients with SDB and improve their prognosis in cardiac function. Further studies will still be needed to assess the benefit of it.